‘Crisis’, control and circulation: Biometric surveillance in the policing of the ‘crimmigrant other’ - Wienroth, Matthias (International journal of police science & management, 2023)
Automated facial recognition, the use of dactyloscopic data and advanced forensic DNA analyses are becoming dominant technological surveillance means for ‘crimmigration’ control. ‘Crimmigration’ describes the increasing criminalisation of migration, based on a perceived ‘crisis’ of mass migration and its assumed negative impact on national stability and welfare, materialising in overlapping crime and migration control regimes. We analyse the policing of migration through biometric technologies as the reproduction of social practices of security against crime. By combining concepts of social practices and ethical regimes, we suggest that biometric ethical regimes are constituted by social practices working towards legitimising the use of biomaterials and biodata. This analytical synthesis supports us in exploring how biometric technologies deployed in the policing of crime circulate into the policing of migration and vice versa. First, technologies as materials (DNA, fingerprints, facial images, analysis kits, databases, etc.) are inscribed with assumptions about validating identity and suspicion, and are increasingly made accessible as data across policy domains. Second, forensic competence moves in abstracted forms of expertise independent of context and ethics of application, creating challenges for reliable and legitimate technology deployment. Third, biometric technologies, often portrayed as reliable, useful, accurate policing tools, travel from crime into migration control with meanings that construct generalised criminal suspicion of migrants. To evidence the complexity and difficulty of achieving accountability and responsibility for the ethical governance of biometric technologies in policing, we trace how the goals, risks, benefits and values of biometric technologies are framed, and how the legitimacy of their deployment in policing of migration is constructed and negotiated.